2016
DOI: 10.3846/16484142.2016.1189960
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Asphalt Texture Roughness on Friction Evolution for Wheeled Vehicles

Abstract: Novelty of the research lies in understanding the safety advantages of asphalt made using advanced pavement design process -compact asphalt pavement installation. Variation of tyre-road friction coefficient for this type of pavement design is new and little-studied phenomenon. The present study focuses on the research into tyre-pavement interaction on dry asphalt pavement surfaces to quantify the effect of microprofile on vehicle performance in establishing its braking conditions. The data on a number of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Vehicle components wear, rolling resistance and discomfort properties are sensitive to longer wavelengths (unevenness and partly mega-texture), while friction between the tyre and the road interacts at mega, macro and micro-texture levels. Moreover, two types of pavement profile waves are specified at the size of the tyre-asphalt contact area: short waves are 3-6 mm in length, and long waves are 20-30 mm [32]. This particular research demonstrates that the 1 mm maximum height of micro-irregularities has been found until adhesion tends to increase; however, this regularity is not applicable for rough surfaces.…”
Section: Related Workmentioning
confidence: 89%
“…Vehicle components wear, rolling resistance and discomfort properties are sensitive to longer wavelengths (unevenness and partly mega-texture), while friction between the tyre and the road interacts at mega, macro and micro-texture levels. Moreover, two types of pavement profile waves are specified at the size of the tyre-asphalt contact area: short waves are 3-6 mm in length, and long waves are 20-30 mm [32]. This particular research demonstrates that the 1 mm maximum height of micro-irregularities has been found until adhesion tends to increase; however, this regularity is not applicable for rough surfaces.…”
Section: Related Workmentioning
confidence: 89%
“…Wear on vehicle components, rolling resistance, and discomfort properties are sensitive to longer wavelengths (unevenness and partly megatexture), while friction between tyres and the road interacts at mega-, macro-, and microtexture levels. Moreover, two types of pavement profile wave sizes have been specified in the tyre-asphalt contact area: short waves are 3-6 mm in length and long waves are 20-30 mm [32]. This particular study demonstrated that the maximum height of 1 mm micro-irregularities were found until adhesion tended to increase; however, this regularity was not applicable for rough surfaces.…”
Section: Related Workmentioning
confidence: 93%
“…In addition, tires help to ensure the vehicles stability on the road. Smaller width of the tire reduces the adhesion to the dry road surface, but facilitates wet driving and reduces the tire noise and fuel consumption [1][2][3].…”
Section: Introductionmentioning
confidence: 99%